Superoxide mediated oxidative cleavage of some electron accepting systems using tetraethylammonium bromide as phase-transfer catalyst - Singh S.; Singh K.N. (My University, 2025)
Various electron accepting substrates have been efficiently cleaved to carboxylic acid or ketone in good yield under the mild reaction conditions of tetraethylammonium superoxide.